2016
DOI: 10.1152/ajpheart.00500.2016
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous initiation of premature ventricular complexes and arrhythmias in type 2 long QT syndrome

Abstract: The occurrence of early afterdepolarizations (EADs) and increased dispersion of repolarization are two known factors for arrhythmogenesis in long QT syndrome. However, increased dispersion of repolarization tends to suppress EADs due to the source-sink effect, and thus how the two competing factors cause initiation of arrhythmias remains incompletely understood. Here we used optical mapping and computer simulation to investigate the mechanisms underlying spontaneous initiation of arrhythmias in type 2 long QT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 73 publications
9
50
0
Order By: Relevance
“…For example, in an early experimental study [17], Damiano and Rosen showed that phase-2 EADs cannot propagate as premature ventricular complexes (PVCs) while phase-3 EADs can propagate as PVCs. This was also shown in our simulation studies [18][19][20]. Therefore, understanding what determine the EAD amplitude and takeoff potential may provide insights into EAD propagation to produce PVCs.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…For example, in an early experimental study [17], Damiano and Rosen showed that phase-2 EADs cannot propagate as premature ventricular complexes (PVCs) while phase-3 EADs can propagate as PVCs. This was also shown in our simulation studies [18][19][20]. Therefore, understanding what determine the EAD amplitude and takeoff potential may provide insights into EAD propagation to produce PVCs.…”
Section: Introductionsupporting
confidence: 77%
“…Cm is the membrane capacitance which was set as Cm=1 F/cm 2 . We simulated six ventricular AP models: the 1991 Luo and Rudy (LR1) guinea pig model [26]; the 1994 Luo and Rudy (LRd) guinea pig model in a modified version [27]; the UCLA (HUCLA) rabbit model with modifications by Huang et al [20]; the 2004 ten Tusscher et al (TP04) human model [28]; the Grandi et al (GB) human model [24]; and the O'Hara et al (ORd) human model [29].…”
Section: Action Potential Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the great advances in understanding the genetic basis of LQTS, the mechanisms resulting in arrhythmia susceptibility are less well understood. The occurrence of early/late afterdepolarizations and increased dispersion of repolarization are thought to play a role in arrhythmogenesis . In LQTS, the decrease in net outward current leads to increased calcium uptake via voltage dependent Ca 2+ channels on the myocardial cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of early/late afterdepolarizations and increased dispersion of repolarization are thought to play a role in arrhythmogenesis. 20 In LQTS, the decrease in net outward current leads to increased calcium uptake via voltage dependent Ca 2+ channels on the myocardial cell membrane. This net increase in inward Ca 2+ flow leads to Ca 2+ -dependent calcium release from the sarcoplasmic reticulum in the submembrane intracellular space which in turn leads to new Na + inward current via Ca 2+ -Na + exchange, triggering afterdepolarization-mediated premature ventricular complexes, which act as triggers of the arrhythmia.…”
Section: Molecular Mechanismsmentioning
confidence: 99%